3
$\begingroup$

How to prove that for $a>0$:

  • $\int_{0}^{\frac{\pi}{2}}\text{erf}(\sqrt{a}\cos(x))\text{erf}(\sqrt{a}\sin(x))\sin(2x)dx=\frac{e^{-a}-1+a}{a}$
  • $\int_{0}^{\frac{\pi}{2}}\text{erf}\ ^2(\sqrt{a}\cos(x))\cos^2(x)dx+\int_0^1 \frac{e^{-\frac{a(1+x^2)}{2}}}{1+x^2}\left(I_0\left(\frac{a(1+x^2)}{2}\right)-I_1\left(\frac{a(1+x^2)}{2}\right)\right)dx=\frac{\pi}{4}$

Here erf denotes error function and $I_\nu$ Bessel. These identities arises from J. M. Borwein's Experiments in mathematics: Computational paths to discovery but the literature offers no proof. Any help will be appreciated!

$\endgroup$
4
  • 2
    $\begingroup$ It's always preferable to to a single integral per post. Perhaps if you'd edit one integral out you will obtain more success. I haven't checked if it helps for the general case, but for $a=1$ the first integral can be found here. $\endgroup$ – Zacky May 2 '20 at 18:21
  • 1
    $\begingroup$ Could you please check the expression for the second integral. I found the following result $$\mathcal{I}_2=\frac{\pi}{4}-\int_0^1\frac{e^{-\frac{a}{2}(1+t^2)}}{1+t^2}\left[I_0\left(\frac{a}{2}(1+t^2) \right)-I_1\left(\frac{a}{2}(1+t^2) \right)\right]\,dt$$ which seems to be numerically correct. $\endgroup$ – Paul Enta May 3 '20 at 17:00
  • $\begingroup$ @PaulEnta Thank you. Do you mean that $\int_{0}^{\frac{\pi}{2}}\text{erf}\ ^2(\sqrt{a}\cos(x))\cos^2(x)dx+\int_0^1 \frac{e^{-\frac{a(1+x^2)}{2}}}{1+x^2}\left(I_0\left(\frac{a(1+x^2)}{2}\right)-I_1\left(\frac{a(1+x^2)}{2}\right)\right)dx=\frac{\pi}{4}$? $\endgroup$ – Iridescent May 12 '20 at 3:18
  • $\begingroup$ @Editprofileandsettings Yes, this is the result I obtained using the integral representation here of $\operatorname{erf}^2$. $\endgroup$ – Paul Enta May 12 '20 at 8:36
3
$\begingroup$

As noted by @Zacky the first result can be adapted from this answer from @DrZafarAhmedDSc. Using the series expansion \begin{equation} \operatorname{erf}(z)= e^{-z^2} \sum_{n=0}^{\infty} \frac{z^{2n+1}}{\Gamma(n+3/2)}. \end{equation} we have \begin{align} \mathcal{I}_1&=\int_{0}^{\frac{\pi}{2}}\operatorname{erf}(\sqrt{a}\cos(x))\operatorname{erf}(\sqrt{a}\sin(x))\sin(2x)dx\\ &=2e^{-a}\int_{0}^{\frac{\pi}{2}}\sum_{n=0}^\infty\sum_{m=0}^\infty a^{n+m+1}\frac{\cos^{2n+2}x}{\Gamma(n+3/2)}\frac{\sin^{2m+2}x}{\Gamma(m+3/2)}\,dx\\ &=e^{-a}\sum_{n=0}^\infty\sum_{m=0}^\infty a^{n+m+1}\frac{B(n+3/2,m+3/2)}{\Gamma(n+3/2)\Gamma(m+3/2)}\\ &=e^{-a}\sum_{n=0}^\infty\sum_{m=0}^\infty\frac{a^{n+m+1}}{(n+m+2)!} \end{align} where the Beta integral was used. Now the double summation can be rearranged as \begin{align} \mathcal{I}_1&=a^{-1}e^{-a}\sum_{m=0}^\infty\sum_{p=m}^\infty\frac{a^{p+2}}{(p+2)!}\\ &=a^{-1}e^{-a}\sum_{p=0}^\infty\sum_{m=0}^{p}\frac{a^{p+2}}{(p+2)!}\\ &=a^{-1}e^{-a}\sum_{p=0}^\infty\frac{(p+1)a^{p+1}}{(p+2)!}\\ &=a^{-1}e^{-a}\left( a\sum_{p=0}^\infty\frac{a^{p+2}}{(p+1)!} -\sum_{p=0}^\infty\frac{a^{p+2}}{(p+2)!}\right)\\ &=a^{-1}e^{-a}\left[a\left( e^a-1 \right)-\left( e^a-1-a \right)\right]\\ &=\frac{1}{a}\left( e^{-a}-1+a\right) \end{align} as proposed.


For the second formula, we use the integral representation of $\operatorname{erf}^2$ here: \begin{equation} \int_{0}^{1}\frac{e^{-\alpha t^{2}}}{t^{2}+1}\mathrm{d}t=\frac{\pi}{4}e^{a}\left(1-(% \operatorname{erf}\sqrt{\alpha})^{2}\right) \end{equation} (This expression can be derived from the integral definition of $\operatorname{erf}$, by interpreting the product of integrals as a double integral in the unit square and by expressing it in polar coordinates). Then, \begin{equation} \operatorname{erf}^2(\sqrt{a}\cos(x))=1-\frac{4}{\pi}\int_0^1e^{-a(1+t^2)\cos^2x}\frac{dt}{1+t^2} \end{equation} which can be plug into the integral \begin{align} \mathcal{I}_2&=\int_{0}^{\frac{\pi}{2}}\operatorname{erf}^2(\sqrt{a}\cos(x))\cos^2(x)\,dx\\ &=\int_{0}^{\frac{\pi}{2}}\left[1-\frac{4}{\pi}\int_0^1e^{-a(1+t^2)\cos^2x}\frac{dt}{1+t^2}\right]\cos^2x\,dx\\ &=\frac{\pi}{4}-\frac{2}{\pi}\int_0^1\frac{e^{-\frac{a}{2}(1+t^2)}dt}{1+t^2}\int_{0}^{\frac{\pi}{2}}e^{-\frac{a}{2}(1+t^2)\cos2x }\left( 1+\cos 2x \right)\,dx\\ &=\frac{\pi}{4}-\frac{1}{\pi}\int_0^1\frac{e^{-\frac{a}{2}(1+t^2)}dt}{1+t^2}\int_{0}^{\pi}e^{\frac{a}{2}(1+t^2)\cos y }\left( 1-\cos y \right)\,dy\\ &=\frac{\pi}{4}-\int_0^1\frac{e^{-\frac{a}{2}(1+t^2)}}{1+t^2}\left[I_0\left(\frac{a}{2}(1+t^2) \right)-I_1\left(\frac{a}{2}(1+t^2) \right)\right]\,dt \end{align} where the classical integral representation for the modified Bessel functions (DLMF) was used. This result corresponds to te proposed formula.

$\endgroup$
0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.